2022
DOI: 10.1002/adfm.202112764
|View full text |Cite
|
Sign up to set email alerts
|

The Fluorine‐Rich Electrolyte as an Interface Modifier to Stabilize Lithium Metal Battery at Ultra‐Low Temperature

Abstract: Lithium (Li) metal batteries (LMBs) are still limited by lithium dendrite growth and solvated structure at low temperatures. A stable solid electrolyte interface (SEI) and solvent sheath structure are the future directions of liquid metal battery development. However, most artificial SEIs and electrolytes cannot meet the original objective of high conductivity and low nucleation potential multifunctional design. To address this challenge, an electrolyte with excellent high current density and low‐temperature p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…The Li x PO y F z and chemisorbed fluorine were distinguished only on the anode surface and were absent after etching, so they were caused by the contact with trace water in the measurement. 22,29,30 The XPS data after etching confirmed that the main inorganic ingredients of Li 2 CO 3 , Li 2 O, and LiF are close for the NG and PG180-1 anodes. Owing to the low addition of PVDF modifier and the coexistence of F-containing binder of PVDF and electrolyte of LiPF 6 , the difference in XPS information obtained from the NG and PG180-1 anodes is not unambiguous, so other techniques were adopted to reveal the modification mechanism.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…The Li x PO y F z and chemisorbed fluorine were distinguished only on the anode surface and were absent after etching, so they were caused by the contact with trace water in the measurement. 22,29,30 The XPS data after etching confirmed that the main inorganic ingredients of Li 2 CO 3 , Li 2 O, and LiF are close for the NG and PG180-1 anodes. Owing to the low addition of PVDF modifier and the coexistence of F-containing binder of PVDF and electrolyte of LiPF 6 , the difference in XPS information obtained from the NG and PG180-1 anodes is not unambiguous, so other techniques were adopted to reveal the modification mechanism.…”
Section: Resultsmentioning
confidence: 66%
“…The surface SEI mainly contains Li 2 CO 3 (Li 1s at 55.4 eV and O 1s at 531.7 eV , ), Li x PO y F z (F 1s at 687 eV, O 1s at 534.0 eV, and Li 1s at 56.0 eV ), traces of LiF (F 1s at 686.5 eV and Li 1s at 57.0 eV ), and chemisorbed fluorine (F 1s at 684.68 eV), while the etched surface is dominantly comprised of LiF, a minute amount of Li 2 O (Li 1s at 55.6 eV and O 1s at 529.8 eV , ), and Li 2 CO 3 . The Li x PO y F z and chemisorbed fluorine were distinguished only on the anode surface and were absent after etching, so they were caused by the contact with trace water in the measurement. ,, The XPS data after etching confirmed that the main inorganic ingredients of Li 2 CO 3 , Li 2 O, and LiF are close for the NG and PG180-1 anodes. Owing to the low addition of PVDF modifier and the coexistence of F-containing binder of PVDF and electrolyte of LiPF 6 , the difference in XPS information obtained from the NG and PG180-1 anodes is not unambiguous, so other techniques were adopted to reveal the modification mechanism.…”
Section: Resultsmentioning
confidence: 79%
“…25 For batteries equipped with lithium metal anodes, stable cycling ranging between À40 C to even À85 C has been achieved by leveraging unique combinations of uorinated electrolytes. 26,27 These results highlight the need for discovering new solvents or solvent combinations that can provide high dielectric permittivity, low dynamic viscosity, and interface stabilizing properties.…”
Section: Introductionmentioning
confidence: 98%
“…Dendrites can pierce the separator, causing several safety issues such as short circuit, thermal runaway and explosion. [19][20][21][22][23][24] To address the problem of lithium dendrite growth, researchers have pioneered several strategies to stabilize lithium metal anodes, such as constructing artificial solid electrolyte interface (SEI) films, [25][26][27] electrolyte optimization, [28][29][30][31][32][33] and designing structural lithium metal anode hosts. [34][35][36][37][38][39][40][41] The first two methods can inhibit the growth of lithium dendrites to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…To address the problem of lithium dendrite growth, researchers have pioneered several strategies to stabilize lithium metal anodes, such as constructing artificial solid electrolyte interface (SEI) films, [25–27] electrolyte optimization, [28–33] and designing structural lithium metal anode hosts [34–41] . The first two methods can inhibit the growth of lithium dendrites to a certain extent.…”
Section: Introductionmentioning
confidence: 99%